Evaluasi Penerapan Sistem Working Permit Sebagai Upaya Pendukung Pelaksanaan K3 Di PT RDM Bekasi - Novia Dwi Cahya; Herlina Herlina (Jurnal Persada Husada Indonesia, 2021)
Certain job operations carry a higher risk and require tight controls. Work permit is a work permit document that refers to the Occupational Health and Safety Management System (SMK3) to ensure that work is carried out safely and efficiently. This study aims to evaluate the application of the working permit system as an effort to support the implementation of K3 at PT RDM Bekasi. The design of this research is qualitative, with a research focus on the working permit system from the planning stage, process stage and completion stage. A total of 8 variables to be studied are coordination, planning, hazard assessment, display of permit, revalidation, return, local inspection, suspension and cancellation of overrides. The research was conducted from March to June 2021. The informants of this study were 4 workers in the cleaning service section. Data taken through interviews and observations as well as document review for secondary data. Data analysis using triangulation. Research conclusion: The preparation phase consists of coordination, planning and hazard assessment and in accordance with the International Association of Oil and Gas procedures. The process stage consists of display of permit, revalidation, and suspension. At the revalidation stage (permit extension) is not carried out at PT RDM, if the permit period. The completion stage consists of returns, local inspections, cacellation of overrides. This stage has been carried out well, but the EHS Officer did not record/recapitulate. The working permit system or work permit is a permit system written in a form called a working permit which is applied when doing work in a hazardous area that is considered to be able to cause an accident.